Induction of Tissue Factor Synthesis in Human Umbilical Vein Endothelial Cells Involves Protein Kinase C - Pettersen, Kjell Sverre; Wiiger, Merete Thune; Narahara, Nobuhiro; Andoh, Kiyoshi; Gaudernack, Gustav; Prydz, Hans (Thrombosis and Haemostasis, 1992)
Incubation of human umbilical vein endothelial cells with one of the following compounds: endotoxin, recombinant interleukin-1β, recombinant tumor necrosis factor α, allogenic lymphocyte subpopulations or phorbol ester resulted in significant induction of tissue factor synthesis. Diacylglycerol had the same effect and also enhanced synergistically the induction caused by endotoxin and interleukin-1β. Two different inhibitors of protein kinase C, H7 and sphingosine, inhibited tissue factor synthesis at concentrations which did not depress protein synthesis in general, suggesting that protein kinase C is involved in the processes leading to tissue factor synthesis. Cells down-regulated for the tissue factor response to TPA responded essentially normally to endotoxin and interleukin-1 with regard to tissue factor synthesis.